A new 24-membered macrolide shows insecticidal activity against Pieris rapae potentially through induction of programmed cell death. Issue 1 (1st January 2019) - Zhang, Yang; Fan, Yangyang; Gao, Jufang; Xu, Wenping; Xu, Zhiping; Liu, Yutian; Li, Zhong; Tao, Liming
ABSTRACT: Pieris rapae is one of the most destructive pests to cabbage around the world and it has developed resistance to present pesticides. 5′-Epi-SPA-6952A was a new 24-membered macrolide isolated from the cultured broth of Streptomyces diastatochromogenes . The aim of this study was to confirm its insecticidal activity against Pieris rapae in field condition, and investigate its potential active mechanism in the cellular level. The results of field experiments showed that the control effects for Pieris rapae reached 79.33% at 45 g/hm 2 after 24 h. Meanwhile, we demonstrated that 5′-Epi-SPA-6952A could inhibit the proliferation of Sf9 cells, induce the DNA damage and enhance the programmed cell death. Intracellular biochemical assay indicated that the cytotoxicity of 5′-Epi-SPA-6952A may be associated with the activity of mitochondrial apoptotic pathways or AMPK/mTOR-mediated autophagy. In conclusion, this study suggests a possible application of 5′-Epi-SPA-6952A as a potential insecticide against Pieris rapae in agriculture.